Metabolic analysis of canine peripheral blood mononuclear cells treated ex vivo with dexamethasone. (January 2016) - Nozawa, Satoshi; Sato, Touko; Katayama, Kinya; Ishioka, Katsumi; Sako, Toshinori; Arai, Toshiro; Tazaki, Hiroyuki
Highlights: Glucocorticoids reduced the catabolic reaction of glucose in canine PBMCs. Dexamethasone decreased ATP in canine PBMCs. Dexamethasone decreased pyruvic acid and metabolites of the TCA cycle. Glucocorticoids decrease ATP production in the TCA cycle and suppress the glycolytic pathway. Abstract: In dogs, hyperadrenocorticism (HAC) is associated with insulin resistance and diabetes does progress with HAC. There are significant differences in the transcriptomic and proteomic patterns of activated T cells, which parallel the findings in muscle tissues. The aim of this study was to assess how glucocorticoids affect intracellular metabolites in canine peripheral blood mononuclear cells (CnPBMCs) using dexamethasone. A total of 96 metabolites were identified by capillary electrophoresis time-of-flight mass spectrometry (CE-TOFMS). After incubation with dexamethasone, the metabolites glucose 1-phosphate, glucose 6-phosphate, fructose 6-phosphate, sedoheptulose 7-phosphate and acetyl-CoA were significantly increased. However, ATP, CTP, dATP, pyruvic acid and NADP + were significantly decreased. These results show that a glucocorticoid reduces the catabolic reaction of glucose and accordingly decreases the glucose requirements of CnPBMCs.